PERNIKAHAN LINTAS AGAMA DI KECAMATAN AEK NATAS KABUPATEN LABUHAN BATU UTARA PROVINSI SUMATERA UTARA - Siti Robiah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
The background of writer to undertake this work is the incompatibility of wedding implementation which took place in the District Aek Natas Labuhan Batu Utara regency. Implementation of their marriage were affected their marriage, because the purposes of marriage did not match the qualifying criteria of marriage and they tend to choose partners who has different beliefs with them. According to that, the writer wanted to know about the cross religion marriage that occurred in the district of Aek Natas. The form of the research is a field research using qualitative data, that a study based on the meaning contained in each of symptoms or existing events to collect data and analyze it on the fields. The source of data in this study are the perpetrators of marriage across religion, society, and community leaders concerned on research were called the key informants to assist authors in data gathering. In data gathering, the method that author used is observation and interview. From the research it can be concluded that the factors causing the interfaith marriage is due to a sense of love and affection, economic factors, promiscuity and the lack of religious education from parents to children, and the resulting the negative impact on the family such as a gap of the relationship, especially with parents, to feel isolated by their communities, the unrecorded marriage by the government, and according to the law of religion, the marriage is haram. The positive effect is the existence of religious tolerance in their households and increasing knowledge about different religious. Fenomena pernikahan yang terjadi di Kecamatan Aek Natas Kabupaten Labuhan Batu Utara yang mengakibatkan pengaruh yang berdampak pada pernikahan mereka, karena pernikahan yang mereka laksanakan tidak sesuai dengan kriteria syarat pernikahan dan mereka cenderung memilih pasangan yang berbeda keyakinan dengan mereka. Berdasarkan hal tersebut penulis ingin mengetahui tentang pernikahan lintas agama yang terjadi di Kecamatan Aek Natas. Dari penelitian yang penulis lakukan dapat diambil kesimpulan bahwa faktor penyebab pernikahan lintas agama adalah dikarenakan rasa cinta dan kasih sayang, faktor ekonomi, pergaulan bebas dan kurangnya pendidikan agama dari orang tua terhadap anak, dan mengakibatkan dampak dari pernikahan tersebut adalah dampak negatifnya yaitu terhadap keluarga terjadi kesenjangan dalam berhubungan dengan keluarga terutama orangtua, terhadap masyarakat merasa terisolasi dengan mereka, terhadap negara pernikahannya tidak diakui, dan terhadap agama hukum pernikahannya adalah haram. Dampak positifnya adalah adanya sikap toleransi dalam beragama dalam rumah tangga mereka dan bertambahnya ilmu tentang agama yang berlainan dengannya.